2023
DOI: 10.1039/d2cc06957a
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-induced reactions of methylenecyclopropanes (MCPs)

Abstract: Diverse visible-light-induced transformations for methylenecyclopropanes (MCPs) have been reported in recent years, attracting significant attention from synthetic chemists. As readily accessible strained molecules, MCPs have enough reactivity to selectively generate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 212 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…In our previous study, the flower-like Fe 3 O 4 is more conducive to enhancing bone regeneration. 26 In addition, the TEM images showed that the flower-like Fe 3 O 4 nanoparticles with a diameter of about 100 nm was self-assembled by smaller magnetic nanoparticles (about 20 nm), as shown in Figure 1b. Figure 1c revealed the morphology of PDA-coated nanoparticles.…”
Section: Preparation and Characterization Of Magnetic Nanoparticlesmentioning
confidence: 91%
See 1 more Smart Citation
“…In our previous study, the flower-like Fe 3 O 4 is more conducive to enhancing bone regeneration. 26 In addition, the TEM images showed that the flower-like Fe 3 O 4 nanoparticles with a diameter of about 100 nm was self-assembled by smaller magnetic nanoparticles (about 20 nm), as shown in Figure 1b. Figure 1c revealed the morphology of PDA-coated nanoparticles.…”
Section: Preparation and Characterization Of Magnetic Nanoparticlesmentioning
confidence: 91%
“…The Fe 3 O 4 was synthesized via a simple solvothermal process as our previous study. 26 Briefly, the sodium dodecyl sulfate (SDS, 0.875 g, Keshi, China) and FeCl 3 Á6H 2 O (7 mmol, Keshi, China) were dissolved in ethylene glycol (EG, 70 mL, Keshi, China) with ultrasonication for 15 min. Then, 2-Aminoethanol (ETA, 5.25 mL, Keshi, China) was added into the above solution with vigorous stirring for 30 min.…”
Section: Synthesis Of Fe 3 Omentioning
confidence: 99%
“…Visible light-mediated chemical transformations have become a powerful tool in synthetic chemistry 1 and materials science 2 for the efficient construction of novel chemical skeletons under mild conditions in the last decade. On the basis of visible light-mediated reaction modes of single electron transfer (SET) and energy transfer (EnT), various robust organic transformations can be achieved under mild conditions, such as C–H bond functionalizations, 3 C–C and C–X (X = heteroatom) bond formations as well as their selective cleavage and the subsequent downstream functionalizations and so on.…”
Section: Introductionmentioning
confidence: 99%
“…) through an electron transfer process. 6 Profiting from the low O 2dependent characteristic, the achievement of type-I PDT is not easily influenced by O 2 concentration, providing a reliable approach for tumor therapy. 7 Besides, combined PDT and photothermal therapy (PTT) is regarded as an efficient method to achieve better anti-tumor outcomes.…”
mentioning
confidence: 99%